1991
DOI: 10.1136/gut.32.8.913
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of tumour necrosis factor alpha in childhood chronic inflammatory bowel disease.

Abstract: Serum tumour necrosis factor a (TNFa) concentrations were measured by enzyme linked immunoadsorbent assay in 31 normal children and during 65 episodes of clinical remission and 54 episodes of relapse in 92 children with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
222
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(234 citation statements)
references
References 46 publications
(10 reference statements)
6
222
1
5
Order By: Relevance
“…Caco2-BBE Cells Overexpressing PHB PHB expression is decreased in IBD patients as well as animal models of colitis (Hsieh et al, 2006;Yeo et al, 2006;Theiss et al, 2007a), whereas TNF-␣ is concomitantly increased (Murch et al, 1991;Braegger et al, 1992). We have shown that TNF-␣ not only decreases PHB promoter activation, but that NF-B is essential for this inhibition (Figure 3).…”
Section: Nf-b Nuclear Translocation Nf-b/dna Binding and Nf-b-mediamentioning
confidence: 91%
See 1 more Smart Citation
“…Caco2-BBE Cells Overexpressing PHB PHB expression is decreased in IBD patients as well as animal models of colitis (Hsieh et al, 2006;Yeo et al, 2006;Theiss et al, 2007a), whereas TNF-␣ is concomitantly increased (Murch et al, 1991;Braegger et al, 1992). We have shown that TNF-␣ not only decreases PHB promoter activation, but that NF-B is essential for this inhibition (Figure 3).…”
Section: Nf-b Nuclear Translocation Nf-b/dna Binding and Nf-b-mediamentioning
confidence: 91%
“…The concentration of TNF-␣ is increased in serum and stool of IBD patients (Murch et al, 1991;Braegger et al, 1992). The increased level of TNF-␣ potentiates the production of other proinflammatory cytokines, further promoting the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…In ulcerative colitis in humans, serum and faecal TNFa levels are increased in active disease. 3,4 In the cotton-top tamarin, in which a spontaneous illness closely resembling human ulcerative colitis frequently develops in captivity, animals treated with CDP571, an antibody to TNFa, gained weight, showed a reduction in disease activity and had reproducible improvements in histology scoring. 5 In steroid-unresponsive Crohn's disease complete SUMMARY Background: Tumour Necrosis Factor-alpha (TNFa) is a pro-in¯ammatory cytokine whose expression is increased in the colonic mucosa of patients with active ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-a is widely held as a key pathogenic factor for colitis pathogenesis in the clinic and experimental models. 47 Anti-C5a attenuates intestinal damage G Chen et al accounts for the therapeutic effects of anti-C5a. Strikingly, our results showed that anti-C5a treatment led to upregulation of IL-10 and TGF-b production in colons, indicating that the efficacy of anti-C5a therapy is also ascribed to enhanced immunomodulatory function of IL-10 and TGF-b.…”
Section: F4/80mentioning
confidence: 99%